PETROGENESIS AND TECTONIC SETTING OF CHROMITE DEPOSITS IN THE SOUTHERN INDIAN CRATON - S S Mense (Innovative Research Thoughts, 2018)
Chromite deposits within the Southern Indian Craton present a significant resource for understanding the geological processes that have shaped the Indian subcontinent. These deposits, primarily located within ultramafic complexes, provide critical insights into the tectonic evolution of the region and the petrogenetic processes that govern the formation of chromitites. This paper explores the geological setting, mineralogical characteristics, petrogenesis, and tectonic context of these chromite deposits, drawing comparisons with global occurrences to highlight both similarities and distinctions. The study further discusses the economic significance of these deposits and the challenges associated with their exploration and sustainable exploitation. Finally, future research directions are suggested, emphasizing the need for advanced geophysical and geochemical techniques to uncover new deposits in underexplored regions.